Pengaruh Perbandingan Terigu Dengan Tepung Kecambah Kacang Merah (Phaseolus vulgaris (L.) Terhadap Karakteristik Pancake - Arisonna Roring, Lucky; Wisaniyasa, Ni Wayan; Mayun Permana, I Dewa Gede (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 2 (2020): Jurnal ITEPADO - 10.24843/itepa.2020.v09.i02.p02, 2020)
This study was aimed to determine the effect of wheat flour comparison with red bean sprout flour on the characteristics of pancakes and to determine the exact concentration of red bean sprout flour that was able to produce pancakes with the best characteristics. This study used a randomized block design with the ratio of flour and red bean sprouts (100%: 0%, 60%: 40%, 50%: 50%, 40%: 60%, 30%: 70%), repeated three times to obtain 15 units of experiment. The data obtained were then analyzed by variants and if there was any effect on the treatment, then continued with Duncan test. The variables observed were moisture content, ash content, protein content, fat content, carbohydrate levels, coarse fiber content, and sensory characteristics. The results showed that the addition of red bean sprout effected moisture content, ash content, protein content, fat content, carbohydrate content, crude fiber content, colour, aroma, taste, texture, and overall acceptance of pancake. The best characteristic of pancake substitution was 50% wheat flour and 50% red bean sprout flour that produced moisture content 36.14%, ash content 1.86%, fat content 24.15%, protein content 8.31%, carbohydrate content 29.53 %, crude fiber content 16.81%, light brown colour (liked), typical aroma of red beans (liked), soft texture (liked), flavour of red beans (liked), and overall acceptance (liked). Keywords: wheat flour, red bean sprouts, characteristics, pancakes.